Individual-psychological features of a teacher as a factor of students’ retrospective judgments about the studied - Tkachuk, Olha V.; Pasichnyk, Ihor D. (International Journal of Psychosocial Rehabilitation, 2020)
The article is based on the theoretical analysis of the notion of the following individual-psychological features of a teacher in the process of educational activity: the level of metacognitive involvement in the activity, the type of professional position as a teacher, individual teaching style, style of pedagogical communication. The aim of the article was to determine the role of these features of a teacher in the process of making metacognitive judgments by students in the learning process. The relationship between the level of development of metacognitive involvement, individual teaching style, pedagogical communication style, type of teacher's professional position as educator, and rating of students' judgments has been empirically investigated. A statistically significant correlation was found between student judgment scores and teacher communication style characteristics.